Adaptive Gamified Learning Environment: Innovation in Using Duolingo for Schools to Increase Learning Motivation of Madrasah Ibtidaiyah Students - Muhammad Mushfi El Iq Bali; Faiqatul Hikmah (Jurnal Muara Pendidikan, 2026)
This study analyzes the effect of implementing gamification using Duolingo for Schools on students' motivation to learn English at an Islamic elementary school. The method used is descriptive qualitative with a case study design, involving students, teachers, class guardians, and the head of Madrasah Ibtidaiyah Az-Zainiyah II. Data were collected through participant observation, in-depth interviews, and documentation, which were then analyzed using data triangulation techniques to ensure the validity of the findings. The results show that the use of Duolingo for Schools significantly increases students' learning motivation, reflected in heightened interest, focus, enthusiasm, and active participation in class. Teachers and the head of the school assessed that this method makes learning more interactive, enjoyable, and relevant to the characteristics of the digital generation. The study concludes that gamification strategies through Duolingo for Schools are effective in boosting learning motivation.